Kekuatan Politik Media Sosial: Uji Kasus pada Revolusi Mesir 2011 - Juned, Mansur; Maliki, Musa; Asrudin, M (UI Scholars Hub, 2013)
This article examines that internet social media have influenced the Egypt Revolution from the authoritarian government to the democratic transition. There are two theories: Cyber-Optimist that argues internet social media is significant in changing a rezim and Cyber-Realist that believes internet is a status quo regime's arsenal in controlling their citizen. Based on cyber-optimist argument, this article believes that internet social media is not supporting the authoritarian government of Husni Mubarak in Egypt, but as the citizen's arsenal to change the authoritarian government of Husni Mubarak.